Sensorimotor integration and functional mobility in early-stage Parkinson’s disease: A cross-sectional study using clinically feasible assessments - Mohammad A. ALMohiza; Ravi Shankar Reddy (PLoS ONE, 2026)
Early-stage Parkinson’s disease (PD) often features subtle sensorimotor integration deficits that may precede noticeable motor decline. This study examined how proprioceptive acuity, balance performance, and functional mobility relate to dual-task gait cost (DTC) in individuals with early-stage PD. Forty-six participants with idiopathic PD (Hoehn & Yahr stages I–II) completed assessments including passive ankle joint position sense testing for proprioception, the modified Clinical Test of Sensory Interaction on Balance (mCTSIB), and a reactive stepping task for balance. Gait was evaluated with the 10-Meter Walk Test under single- and dual-task (verbal fluency) conditions, and DTC was calculated from changes in gait speed. Greater proprioceptive error was significantly associated with slower dual-task gait speed (r = –0.52, p < 0.001), higher DTC (r = 0.47, p = 0.002), and increased stride time variability (r = 0.45, p = 0.003). In a multiple regression, proprioceptive error (β = 0.43, p < 0.001) and mCTSIB composite score (β = –0.40, p = 0.004) independently predicted DTC, with a mean of 17.3% (SD = 6.8). Participants who failed the reactive stepping task (n = 18) showed significantly greater proprioceptive error (mean = 4.7° vs. 2.9°, p < 0.001), slower dual-task gait speed (0.84 m/s vs. 1.06 m/s, p < 0.001), and lower verbal fluency scores (mean = 8.2 vs. 11.5 words, p < 0.001). These findings indicate that clinically measurable deficits in proprioception and balance are linked to impaired gait performance and reduced adaptability under cognitive load in early PD. Integrating sensorimotor assessments into early clinical evaluations may support timely, targeted interventions to mitigate mobility decline.